Perianal Comedones: A Rare Incidental Finding - Priscilla R. Powell; Juana Irma Garza-Chapa; Joseph S. Susa; Stephen E. Weis (Case Reports in Dermatological Medicine)
Comedones occur when an overproliferation of keratinocytes blocks sebum secretion in a pilosebaceous duct. Comedones have multiple possible etiologies and contributing factors. While comedones are common to acne, they are also seen in occupational exposures and are associated with certain syndromes. We describe a particularly rare case of comedones at the perianus that is not associated with any known exposure or disease and is a rare incidental finding.